Optimalisasi Proses Digitalisasi UMKM melalui Aplikasi Marketplace berbasis Design Thinking - Sari, Aprilisa Arum; Pramono, Pramono; Saputra, Ilham Trisatdika; Prakoso, Aprilrianto Dirhamdan (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Tourism villages in Boyolali district have enormous potential to boost economic growth, especially MSMEs. However, many MSMEs do not know digital applications. This research aims to optimize the digitalization process of Micro, Small, and Medium Enterprises (UMKM) through the development of a Design Thinking-based marketplace application. This research found the digital needs of UMKM through interviews and thorough analysis. The results show that effective and easily accessible digital products with interactive guidance features, automated inventory management, and easy-to-do market analysis are essential. Two prototypes each with seven main menus, were tested by 15 villagers, teenagers and general participants, using cognitive walkthrough, SEQ, A/B, and UEQ methods. Results showed that Prototype B was superior to Prototype A. In the Cognitive Walkthrough test, Prototype B showed a 100% success rate among teenagers and general participants. SEQ results indicated higher user comfort in Prototype B, with 84.375% of respondents giving the highest score of 5. A/B Testing showed higher interaction in Prototype B on various pages of the app, showing better efficiency. In UEQ aspects, Prototype B also performed better in perspicuity, stimulation, and novelty. These findings confirm that the Design Thinking approach is effective in developing user-friendly apps, helping to accelerate the digital transformation of UMKM in Indonesia.